Unilateral Pseudotumoral Presentation of Cerebral Venous Thrombosis - Pimentel, Leonardo Halley Carvalho (Journal of Health & Biological Sciences, 2014)
Cerebral venous thrombosis (CVT) is an unusual cause of stroke. It is more common in middle-aged women and deep CVT lesions are usually bilateral. CVT can have very diverse clinical presentations and mimic other conditions. We report two women with CVT initially diagnosed as tumors (unilateral pseudotumoral presentation of CVT) successfully treated with intravenous heparin. Early diagnosis was important and completely reversed the symptoms. The diagnosis of CVT should be remembered when clinical picture is compatible even if brain imaging suggests unilateral tumor.